2002
DOI: 10.1002/dc.10166
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic manifestations of cystitis follicularis in urine specimens

Abstract: Four cases of cystitis follicularis diagnosed by urine cytology are presented, and are the first reported in the cytologic literature. Cystitis follicularis (follicular cystitis) is characterized by formation of lymphoid follicles in the lamina propria of the trigonal region of the bladder, and is considered to be the result of repeated bouts of urinary tract infection, usually bacterial, with other pathologic processes contributing to the development and prolongation of the infection. Cytologically it differs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…It has been suggested that follicular cystitis is a response to chronic stimulation, whether inflammatory, infectious, antigenic or neoplastic (Zaharopoulos 2002). Similar to other chronic cystitides, it is likely to be a multifactorial condition involving epithelial dysfunction, neuro-urothelial interactions and chronic inflammation (Sant 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that follicular cystitis is a response to chronic stimulation, whether inflammatory, infectious, antigenic or neoplastic (Zaharopoulos 2002). Similar to other chronic cystitides, it is likely to be a multifactorial condition involving epithelial dysfunction, neuro-urothelial interactions and chronic inflammation (Sant 2002).…”
Section: Discussionmentioning
confidence: 99%
“…trauma, mass effect), anatomical abnormalities (i.e. vestibulovaginal stenosis, recto-urinary fistulas) and there has also been some implication of bladder carcinoma in the formation of follicular cystitis in human beings (Zaharopoulos 2002, Sarma 1970, Trombetta and others 2012, Crawford and Adams 2002, Holt and Sayle 1981). The factors described above were all ruled out in this case by the imaging studies and histopathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytologically it differs from chronic cystitis with prominent lymphocytosis by the presence of cellular elements from the germinal centres of lymphoid follicles, reminiscent of the cytologic findings in follicular cervicitis, with possible additional epithelial cytologic atypias from the overlying urothelium, which frequently undergoes reactive changes (hyperplastic, metaplastic, and ulcerative) [8]. In this patient, persistence of hydronephrosis, hydroureter and residual urine in urinary bladder predisposed to chronic urine infection with acute exacerbations, which resulted in formation of follicular cystitis.…”
Section: Discussionmentioning
confidence: 99%
“…2 A recent publication has shown that FC can be detected cytopathologi-cally in urine specimens. 3 Histologically, numerous plasmacytic cells and lymphocytes with lymphoid follicles scattered within the bladder mucosa and submucosa are seen. These are classically described as well-developed lymphoid follicles containing germinal centers with surrounding lymphocytic collars at regular intervals in the mucosa.…”
Section: Introductionmentioning
confidence: 99%